A new species of the Stenus cephalotes group (Coleoptera, Staphylinidae) from Guangxi, South China - Li, Wen-Rong; Tang, Liang; Li, Li-Zhen (Zootaxa, 2013)
A new species of the Stenus cephalotes group, S. mawenliae sp. n. from Guangxi, South China, is described and illustrated. The latest key to Chinese species of the group is modified to include the new species.